Emotions and Instructed Language Learning: Proposing a Second Language Emotions and Positive Psychology Model - Shao, Kaiqi; Nicholson, Laura J.; Kutuk, Gulsah; Lei, Fei (Frontiers in Psychology, 2020)
Although emotion research and positive psychology (PP) have recently gained strong momentum in the field of second language acquisition (SLA), no conceptual review has been conducted on emotions and language learning from the perspective of PP. To address this gap, this article first introduces the concept and research around PP, and summarizes PP-related constructs which have been tapped in SLA research. Next, it reviews research into emotions and classroom language learning and identifies aspects of PP that have become embedded within second language (L2) emotion research. Finally, by triangulating emotion theories and research in the fields of psychology, education and SLA, we propose a theoretical framework merging three pillars of PP with the antecedents, outcomes and interventions of L2 emotions. The value of this framework to second language pedagogy and research is highlighted in the context of the importance of integrating PP into the area of emotions and instructed SLA.